O ensino de cálculo em cursos superiores de tecnologia: um olhar para o curso de microeletrônica - Santos, Clemente Ramos dos (2019)
This study explored the relationship between the contents of the ‘Calculus’ subject – functions, limits, derivatives, and integrals – and the contents of some professional courses from a higher education program on Microelectronics technology taught at an institution in São Paulo, and to determine the perceptions of teachers about these relationships. The study was conducted according to the theoretical perspective of Mathematics in the Context of the Sciences (MCC), developed by Mexican researcher Patricia Camarena to help examine mathematics teaching in programs intended for non-mathematicians. A qualitative approach was employed to analyze the program’s pedagogic design, the textbooks used for the professional courses, and the textual content from semistructured interviews conducted by the researcher with the course coordinator, three teachers of Calculus and three teachers of professional courses. These documents were analyzed using the Dipcing method (Diseño de programas de estudio de matemáticas en carreras de ingeniería – Design of mathematics study programs in engineering careers), also developed by Camarena in the ambit of one of the phases of the MCC theory. While the analysis of textbooks for the professional courses revealed relationships between the content of Calculus and content specific to these courses, the objectives of the ´Calculus´ subject in the pedagogic design were only loosely related with the specificities of the program. Also, the program’s pedagogic design lacked didactic-pedagogic/teaching-learning strategies for curriculum development—i.e. it provided no pedagogic principles to guide teacher practices. No integration was evident between teachers of ‘Calculus’ and of professional courses, hampering the establishment of strategies for their teaching practices. This situation led to teachers teaching their courses in an isolated fashion. As a result, students may experience difficulties applying Calculus knowledge to solve situational problems proposed in professional courses